(3eHGOF Yde GdEbJUGO (B/s - (3GdhGOj, eMehO MSjfs; (3YHGS, fVGd Ydj s ((3YeGf(B: s (3OGQ GdeSjQI ddfTQ h GdJhRjY(B, s, 2013)
(3eONd YGe ddEbJUGO(B- (3YfGUQ GdEfJGL(B- (3fXQjI GdWdH(B- (3fXQjI GdYQV(B- (3JMOjO GdCKeGf(B- (3GdShb(B- (3fXQjI GdESJgdGc(B- (3GdONd Gdbhej hGdfGJL Gdbhej(B- (3eUGOQ GdWdH Gdcdj(B-(3GdGLhQ hGdHWGdI hGdJVNe(B- (3GdSjGSI GdfbOjI hGdeGdjI(B- (3GdfbhO hGdHfhc(B- (3GdJLGQI GdNGQLjI hGdJfejI GdEbJUGOjIs
(3cTGa eUWdMGJ U(B349(3; GdeQGLY U (B359s
Keywords: (3GdESJgdGcs; (3GdEbJUGOs; (3GdONd Gdbhejs; (3Yde GdEbJUGOs